Challenges and possible solutions for decoding extranasal olfactory receptors. (6th November 2020) - Kalra, Siddhant; Mittal, Aayushi; Bajoria, Manisha; Mishra, Tripti; Maryam, Sidrah; Sengupta, Debarka; Ahuja, Gaurav
Abstract : Olfactory receptors are primarily known to be expressed in the olfactory epithelium of the nasal cavity and therefore assist in odor perception. With the advent of high‐throughput omics technologies such as tissue microarray or RNA sequencing, a large number of olfactory receptors have been reported to be expressed in the nonolfactory tissues. Although these technologies uncovered the expression of these olfactory receptors in the nonchemosensory tissues, unfortunately, they failed to reveal the information about their cell type of origin. Accurate characterization of the cell types should be the first step towards devising cell type‐specific assays for their functional evaluation. Single‐cell RNA‐sequencing technology resolved some of these apparent limitations and opened new means to interrogate the expression of these extranasal olfactory receptors at the single‐cell resolution. Moreover, the availability of large‐scale, multi‐organ/species single‐cell expression atlases offer ample resources for the systematic reannotation of these receptors in a cell type‐specific manner. In this Viewpoint article, we discuss some of the technical limitations that impede the in‐depth understanding of these extranasal olfactory receptors, with a special focus on odorant receptors. Moreover, we also propose a list of single cell‐based omics technologies that could further promulgate the opportunity to decipher the regulatory network that drives the odorant receptors expression at atypical locations. Abstract : The adoption of single‐cell RNA sequencing technologies imparts new means to interrogate the expression of ectopic olfactory receptors at single‐cell resolution. In addition to the quantitative estimation of the cellular transcript, it also offers information about their cell‐type of origin. These and related technologies will spearhead the research on ectopic olfactory receptors, and deconvolute their potential function at the atypical tissue.